NATURE IN IRIS MURDOCH'S THE SEA, THE SEA - G. M. Adhyanggono (Celt: A Journal of Culture, English Language Teaching & Literature, 2010)
Iris Murdoch ~ The Sea, The Sea is a novel which uses nature as its background or setting. This article particularly intends to give its attention to the aspects of nature delineated in the novel. In other words, this study is aimed at identifying, classifying, and describing aspects or elements of nature in it. It is also important to describe the relationship between these aspects and the story, as well as the characters. In addition, the tenets of "ecocriticism'' are used as the parameter toprove that the novel is still "anthropocentric", or a human-centred work of art. The reason why such a method is used is simply because it is concerned with nature. Nevertheless, the study in this case can not be seen as a "pure" ecological reading because it merely uses ecological boundaries to prove the anthropocentricity of the novel. However, since some principles in the ecocriticism are used, it is inevitable not to mention or explain what this ecocriticism deals with.